Comparative Analysis of Interregional and Intersectoral Mobility in Russia - Vakulenko, Elena S. (Economy of Regions, 2020)
One of the most important characteristics of the labour market is labour mobility that allows assessing the economic efficiency of labour. A comparative analysis is necessary for determining the degree of mobility. In terms of spatial and sectoral characteristics, the paper assesses the degree and dynamics of mobility in the Russian labour market based on previously published studies, as well as the authors’ findings. To determine the degree of mobility, the research uses various approaches, applying both direct (mobility costs, transition matrices) and indirect indicators (structural unemployment, wage differentiation, unemployment rate, gross regional product (GRP)). The analysis uses the data of the Russia Longitudinal Monitoring Survey — Higher School of Economics (RLMS-HSE) and Federal State Statistic Service (Rosstat) for 2000–2016. The obtained results demonstrate a relatively low intersectoral and interregional mobility in Russia compared to Organisation for Economic Co-operation and Development (OECD) countries. Low intersectoral mobility may indicate weak exchangeability of the sectors and high mobility costs. The largest number of transitions is observed in trade, where employees do not need any specific knowledge. Generally, other transitions are made between related sectors that require similar knowledge from employees. The lowest intersectoral mobility is characteristic for the education and health sectors. According to the Shorrocks index, in Russia, interregional mobility is lower than intersectoral mobility. Low spatial mobility is explained by high migration costs, including those associated with “poverty traps”, the peculiarity of statistical accounting of migrants and the size of Russian regions. The obtained results are correct for the examined period and the applied criteria. The changes in labour mobility in Russia caused by global digitalisation of the economy and the transition to remote working require a separate study.